Electrical muscle stimulation after immediate nerve repair reduces muscle atrophy without affecting reinnervation. Issue 2 (2nd May 2013) - Willand, Michael P.; Holmes, Michael; Bain, James R.; Fahnestock, Margaret; De Bruin, Hubert
ABSTRACT: Introduction: Electrical stimulation of denervated muscle has been shown to minimize atrophy and fibrosis and increase force in animal and human models. However, electrical stimulation after nerve repair is controversial due to questions of efficacy. Methods: Using a rat model, we investigated the efficacy of short‐term electrical muscle stimulation for increasing reinnervation and preventing muscle atrophy. After tibial nerve transection and immediate repair with the fibular nerve, 1 month of electrical stimulation was applied 5 days/week for 1 hour to the gastrocnemius muscle via implanted electrodes. Results: After 2 months of further recovery without stimulation, muscle weights, twitch forces, and type I fiber areas were significantly greater in stimulated animals than in repaired controls without stimulation. Motor unit size and numbers were not different between the 2 groups. Conclusions: Short‐term electrical muscle stimulation after nerve repair significantly reduces muscle atrophy and does not affect motor reinnervation. Muscle Nerve, 48: 219–225, 2013